Contractive Maps in Locally Transitive Relational Metric Spaces - Mihai Turinici (The Scientific World Journal)
Some fixed point results are given for a class of Meir-Keeler contractive maps acting on metric spaces endowed with locally transitive relations. Technical connections with the related statements due to Berzig et al. (2014) are also being discussed.